2013
DOI: 10.1021/ar400151n
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal-Sized Metal–Organic Frameworks: Synthesis and Applications

Abstract: Colloidal metal-organic frameworks (CMOFs), nanoporous colloidal-sized crystals that are uniform in both size and polyhedral shape, are crystals composed of metal ions and organic bridging ligands, which can be used as building blocks for self-assembly in organic and aqueous liquids. They stand in contrast to conventional metal-organic frameworks (MOFs), which scientists normally study in the form of bulk crystalline powders. However, powder MOFs generally have random crystal size and shape and therefore do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
246
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(250 citation statements)
references
References 51 publications
2
246
0
2
Order By: Relevance
“…Furthermore, it has been indicated that ZIF-67's isostructure ZIF-8 exhibited structural instability under a highly acidic environment (i.e., soaked in a solution at pH = 1 for 24 h) (Sindoro et al, 2013). Nevertheless, the typical pH range of wastewater and aquacultural wastewater is from 4 to 9, and the adsorption time proposed in this study (i.e., 2 h) is relatively short.…”
Section: Effects Of Salts and Ph Of Solution On The Adsorption Capacitymentioning
confidence: 76%
“…Furthermore, it has been indicated that ZIF-67's isostructure ZIF-8 exhibited structural instability under a highly acidic environment (i.e., soaked in a solution at pH = 1 for 24 h) (Sindoro et al, 2013). Nevertheless, the typical pH range of wastewater and aquacultural wastewater is from 4 to 9, and the adsorption time proposed in this study (i.e., 2 h) is relatively short.…”
Section: Effects Of Salts and Ph Of Solution On The Adsorption Capacitymentioning
confidence: 76%
“…These are crystalline materials consisting of metal ions or clusters and organic linker(s) with strong covalent bonds [6,7]. Due to their high porosity, large internal surface area, and high thermal stability (generally >300°C) [7], MOFs have a variety of potential applications in many fields including gas storage [8], catalysis [9,10], drug delivery [11], and chemical sensing [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Among them, an emerging class of nanoparticles is the nanometric porous metal organic frameworks (nanoMOFs), 2−4 whose unique tunable nature enables one to address the highly demanding set of requirements for their application in this field. 5 In this sense, one can select their composition (cation and organic linker) and type of porous architecture that render nanoMOFs both nontoxic and biodegradable and useful to load and deliver active molecules. 6 Their high and regular porosity combined with an internal amphiphilic microenvironment, well adapted to host a wide range of therapeutic guests, leads to exceptionally high payloads and a controlled release of the entrapped drugs under simulated physiological conditions.…”
Section: Introductionmentioning
confidence: 99%